Minimally invasive video-assisted retroperitoneal necrosectomy for long-term complications of pancreatic fistula after pancreatectomy (Revista Argentina de Cirugía, 2025)
Background: Peripancreatic fat necrosis resulting from persistent type B pancreatic fistulas is a common complication of cephalic pancreaticoduodenectomy (CPD) and left pancreatectomy (LP) and usually requires minimally invasive surgical treatment.Objective: The aim of this study was to describe the results of minimally invasive video-assisted retroperitoneal necrosectomy as a therapeutic option in cases of peripancreatic fat necrosis resulting from pancreatic fistulas after pancreatectomy.Material and methods: We conducted a retrospective analysis of a prospective database of pancreatic resections performed between January 2010 and December 2024. Those patients with pancreatic fistula requiring minimally invasive retroperitoneal video-assisted necrosectomy were identified.Results: During the mentioned period, 710 pancreatic resections (505 CDPs and 205 PIs) were reviewed. Two patients (0.028%, 95% CI: 0.00-0.01) presented necrosis of the peripancreatic tissue secondary to the persistence of a pancreatic fistula and persistent fever due to superinfection. Both patients underwent video-assisted retroperitoneal necrosectomy with a favorable outcome.Conclusion: The minimally invasive approach represented a therapeutic option that minimized morbidity and improved the postoperative outcomes
Keywords: fistula; pancreaticoduodenectomy; necrosis; surgery